The Yield Potential Of F6 Generation Of Yellow Common Bean (Phaseolus vulgaris L.) - Andy Soegianto; Bima Fikry (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2016)
The yield potential test is an important step in breeding activity in creating new varieties through evaluation the desired genes on some lines (Basuki, 1995). The value of heritability could indicate that every character observed was genetically influenced which inherited from the parental lines and its interaction with environmental factors. On this basis, this research was conducted at the Sawaulan, Tawang Agro Village, District Karangploso, Malang, East Java. The used materials in this research were three lines of yellow pod common beans of F6generation (CS x GK 50-0-24; CS x GI 63-0-24; and CS x GI 63-33-31), three parental varieties and Lebat-3 variety as check varieties. The completely randomized block design was used by observed 10 samples of plants per plot. This research showed that the three lines of common bean tested had uniformity in all characters evaluated by using quantitative and qualitative analysis. The value of GCV (Genotypic Coefficient of Variance) in every characters evaluated of the tested lines were low criteria and these values were lower than in the check varieties. The low variation indicated the small variation, i.e that the lines were already uniform. The heritability value of some characters observed in the lines were lower, while some other characters still had high heritability value. The heritability in the three lines tested were influenced by environment and genes as well. The character that had high heritability could inherit uniformly the character in concern on the next generation. The high heritability shows that the plant breeding program especially the selection program has been succesful.